Uma intervenção educativa para profissionais de saúde na prevenção de pneumonia associada à ventilação mecânica - Melo, Cristiane Ribeiro de (2008)
Quasi-experimental study, prospective with quantitative approach, performed at the Hospital do Coração in Natal, aimed at verified the existence of difference between the care given by health professionals to the patients under mechanical ventilation (MV) in the Intensive Care Unit, before and after an educative intervention. The population was of 31 professionals, with data collected between november 05 of 2007 to march 27 of 2008. The results show a yong population, female gender, middle level of education, nursing technique, working between 05 and 09 years on nursing profession, and 01 to 04 years on Intensive Care Unit; almost all, never had an kind of training over prevent pneumonia associated to mechanical ventilation; from those that had training, occur on the work place with duration from 12 to 24 hours. About endotracheal intubation, the cuff was tested with a sterilized syringe had a positive change after a educative intervention, increased from 75,0% to 100,0%; the sterile guide was used on 75,0% before and 100,0% after an educative intervention. Regarding endotracheal suction procedure, was not informed to the patient on 72,7% before, however was informed on 56,7% after; the hands was not previously washed 68,5% before, however was 63,3% after the procedure; mask was used on 74,2 % opportunities before and 76,7% after; the aspiration catheter had adequated size on 98,9% observation before and 100,0% after; the gaze was sterilized on 95,7% before and 100,0% after; the ventilator was connected to the patient during the aspiration intervals on 94,4% observation before and 100,0% after; the ambu bag was clean and protected on 76,1% before and 85,7% after; the aspiration catheter was discarded after be used on 98,9% before and 100,0% after; FIO2 was turned to the begging value on 32,9% observation before and 12,0% after; before the procedure 71,9% professions washed their hands and 73,3% after; before, notes of aspiration results were performed on 70,8% observation and 86,7% after. Regarding devices used on respiratory tract, aspirator flasks were not swapped on 84,6% observations before and 71,0% after; daily látex extention change was not performed on 93,6% observation before and 87,1% after; the ambu bag change was not performed on 50,0% observation before even if was duty or unprotected and on 75,8% opportunities was changed, after; nebulization was not prepared with sterile fluids or manipulated aseptically on 65,2% observation before, perhaps was on 71,7% after; before nebulizers were not changed on 65,2% observations, perhaps were on 60,9% after. Concerning ventilator breathing circuits, condense fluids cumulated on circuits were removed on 55,0% opportunities before, and 64,0% after; moisturizer was not filled with sterile water when already had small amount of liquid inside on 78,4% observations before, and 90,2% after; MV circuits were changed on 97,0% observations on presence of visible duty or when presents some kind of failure, before and 98,4% after. About body position, on 51,3% observations the decubitus position change were done before and 78,2% after; fowler position was maitened on 95,5% observations before and 98,2% after; Regarding respiratory physiotherapy, enteral diet was not interrupted before respiratory physiotherapy on 94,9% before and 90,0% after; respiratory physiotherapy devices were not disinfected or sterile on 69,6% observations before but they re on 60,0% after; before the cateter was not tested before introduction enteral diet or medications on 100,0% but after was done on 15,2%. About enteral feeding, intestine motility and measure of stomach contents were not done on 100,0% observations before, but was 15,2% after. We conclude that 05 of 07 valuated procedures in relation to MV, had a significant improvement on quality of care given after educative intervention, when compared before intervention